Impact of Uterine Adenomyosis on Pregnancy Outcomes in Women Undergoing In Vitro Fertilization Treated With a Long-Term Pituitary Downregulation Protocol - Zhang, Jiaxin; Hu, Linli; Bu, Zhiqin; Sun, Yingpu (Frontiers in Endocrinology, 2021)
Background: Some studies have demonstrated that adenomyosis patients can achieve a comparable pregnancy outcome with normal uterus women, while there is no unanimous conclusion at present. Method: A total of 65 adenomyosis patients and 260 frequency-matched control women of endometriosis at a ratio of 1:4 according to age were included into this study. Clinical pregnancy rate, spontaneous abortion rate, and live birth rate were compared between these two groups after controlling other factors. Results: Compared with endometriosis patients, adenomyosis patients had higher AFC (12.71 vs 11.65, P=0.027). Though the two groups had the same number of embryos transferred, adenomyosis patients had obviously declined implantation rate (31.91% vs 46.74%, P=0.005), clinical pregnancy rate (47.06% vs 64.42%, P=0.028), live birth rate (31.37% vs 54.81%, P=0.004), and significantly increased spontaneous abortion rate (33.33% vs 13.43%, P=0.034) as well. Multivariate logistic regression analysis showed that adenomyosis had adverse influences on pregnancy outcome when age and the number of embryos transferred were controlled (adjusted OR=0.361, P=0.003). Conclusion：Even after matched with age, adenomyosis still has adverse influences on the pregnancy outcome of IVF in patients treated with long-term pituitary down regulation protocol.